2006
DOI: 10.1161/01.str.0000227195.46336.93
|View full text |Cite
|
Sign up to set email alerts
|

Is the ABCD Score Useful for Risk Stratification of Patients With Acute Transient Ischemic Attack?

Abstract: Background and Purpose-A 6-point scoring system (ABCD) was described recently for stratifying risk after transient ischemic attack (TIA). This score incorporates age (A), blood pressure (B), clinical features (C), and duration (D) of TIA. A score Ͻ4 reportedly indicates minimal short-term stroke risk. We evaluated this scoring system in an independent population. Methods-This was a prospective study of TIA patients (diagnosed by a neurologist using the classic Ͻ24-hour definition) hospitalized Ͻ48 hours from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
73
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 18 publications
11
73
1
1
Order By: Relevance
“…17 The presence of ischemic lesions on DWI or large artery occlusion is another predictor for recurrent stroke after TIA. [22][23][24][25][26] Although the association between FVH and poor outcome in patients with IS was demonstrated, 27,28 the association between FVH and recurrence of TIA or IS after TIA has been merely reported. 29 In the present study, Cox proportional hazard analysis showed that recurrence within 90 days after onset was associated with AOL and FVH, as well as coexistence of these 2.…”
Section: Discussionmentioning
confidence: 99%
“…17 The presence of ischemic lesions on DWI or large artery occlusion is another predictor for recurrent stroke after TIA. [22][23][24][25][26] Although the association between FVH and poor outcome in patients with IS was demonstrated, 27,28 the association between FVH and recurrence of TIA or IS after TIA has been merely reported. 29 In the present study, Cox proportional hazard analysis showed that recurrence within 90 days after onset was associated with AOL and FVH, as well as coexistence of these 2.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of our study methodology has been published previously. 6 Informed consent was obtained from all subjects and the protocol was approved by our local Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to validate ABCDbased scoring in independent populations have been generally, 3 but not universally, successful. 4 Some groups have questioned the usefulness of a score that does not incorporate significant carotid disease or other potential cardioembolic source. 5 More importantly, in all ABCD validation exercises, the underlying diagnosis has been assumed to be TIA.…”
mentioning
confidence: 99%